On almost D-optimal first order saturated designs and their efficiency - Koukouvinos, Christos (Utilitas Mathematica, 1997)
The problem of constructing first order saturated designs that are optimal in some sense has received a great deal of attention in the literature. In experimental situations where n two-level factors are involved and n observations are taken, then the D-optimal first order saturated design is an n × n ±1 matrix with the maximum determinant. In this paper we construct almost D-optimal first order saturated designs with n = 29 and n = 22 observations and we compute their D-efficiency.